Genotypic Difference in Growth and Physiological Indices of Grain Amaranth Species under Salinity Stress - Ramani, Divyesh H.; Singh, Anuj Kumar; Prajapati, Nitesh N.; Tiwari, Kapil Kumar; Bhadauria, Hitendra S. (International Journal of Bio-resource and Stress Management, 2023)
The present experiment was conducted during October to February of year 2019−20, to investigate the effect of salinity on morpho-physiological traits and identify the genotype have higher salt tolerance among ten genotypes belongs to three grain Amaranth species. Plant growth traits viz., plant height, shoot and root dry weight decreases with increase in the salinity stress level (EC of 5 and 10 dS m-1) in all the genotypes, however significant (p<0.01) genotypic difference were present among genotypes and GA-5 maintained the maximum growth under salinity. Percent decrease in SDW and RDW was lowest (10.61−23.86 and 10.37 and 26.59) in A. hypochondriachus while in A. cruentus (15.10-29.55 and 12.78-33.09) and A. caudatus (15.15−28.84 and 16.62-34.90). Salinity significantly (p<0.01) decreases the membrane stability, relative water content and leaf potassium content while, leave sodium content increases. As compared to other genotype GA-5 have maximum membrane stability (53.30), relative water content (85.40%), K+ accumulation and minimum Na+ accumulation in leaves.Morpho-physiological traits of grain Amaranthus species are significantly positively correlated with dry shoot biomass (0.649), MSI (0.770), RWC (0.768), chlorophyll (0.908), carotenoid (0.883) and leaf potassium (0.883). It might be concluded that among studied genotypes GA-5 maintained the growth and have higher physiological efficiency results into maximum salt tolerance index also morpho-physiological traits like dry weight, RWC, MSI, Chlorophyll, Carotenoid and leaf potassium content might be utilised for selection of salt tolerant Amaranth genotypes.